(untitled) (Jurnal Kemanusiaan, 2017)
The study includes three government agencies, namely the Royal Malaysian Police (RMP), the National Registration Department (NRD) and the Public Works Department (PWD) in Malaysia. The study on these three government agencies covered the services rendered, functionality, effectiveness and efficiency of their officers. A total of 270 respondents from three government agencies, namely the Royal Malaysian Police (PDRM), the National Registration Department (NRD) and the Public Works Department (PWD) in Malaysia have been selected to answer the questionnaire in this study. The results of the study showed that employee attitudes have a positive relationship on the effectiveness and efficiency of the employee. Meanwhile, the hypothesis on the relationship between attitude of the employees and work productivity was partially accepted. The employee attitude is crucial in Malaysia government agencies to ensure excellent work quality. Therefore, the attitude of the employees should be given serious attention by the Malaysian government to improve the work quality of government agency. Kajian ini merangkumi tiga agensi kerajaan iaitu Polis DiRaja Malaysia (PDRM), Jabatan Pendaftaran Negara (JPN) dan Jabatan Kerja Raya (JKR) di Malaysia. Kajian ke atas tiga buah agensi kerajaan ini adalah merangkumi perkhidmatan yang diberikan, fungsi, keberkesanan serta kecekapan pengawai yang bertugas di agensi-agensi tersebut. Seramai 270 responden dari tiga buah agensi kerajaan iaitu Polis DiRaja Malaysia (PDRM), Jabatan Pendaftaran Negara (JPN) dan Jabatan Kerja Raya (JKR) di Malaysia telah dipilih untuk menjawab soal selidik terlibat dalam kajian ini. Hasil kajian ini menunjukkan sikap pekerja mempunyai hubungan positif dengan keberkesanan kerja dan kecekapan kerja seseorang pekerja. Manakala, sikap pekerja menunjukkan separa hipotesis diterima untuk produktiviti kerja. Sikap pekerja amat penting di agensi-agensi kerajaan Malaysia dalam meningkatkan kualiti kerja cemerlang sesebuah agensi kerajaan. Oleh itu, sikap pekerja ini harus diberikan perhatian yang serius oleh kerajaan Malaysia untuk menambah baik kualiti kerja sesebuah agensi kerjaan Malaysia.